(untitled) (Research, Society and Development, 2022)
Objective: To investigate the effect of expiratory muscle training on the respiratory capacity of children with cleft lip and palate. Methodology: Randomized clinical trial with a longitudinal and prospective period. Study carried out in the specialty outpatient clinics of a Pediatric Hospital in a city in southern Brazil, together with a Federal University. Subjects with cleft lip and palate, between three and 12 years old, already corrected by cheiloplasty and palatoplasty surgeries were included. Subjects with intellectual disabilities or other associated malformations were excluded. Subjects were assessed pre- and post-intervention, as well as reassessed at a 3-month follow-up. The training followed, in both groups, the performance of 3 series of 10 repetitions per week, during six weeks. The Water Group used PEP in Water Seal, while the Respiron Group used Respiron®. Results: Regarding muscle strength and respiratory capacity, all subjects showed statistically significant improvement (p= <0.001). The Water Group showed a statistical difference for vital capacity (p=0.007). The postural data showed no difference between the evaluated periods. Conclusion: Subjects with cleft lip and palate benefit from the use of respiratory incentive devices through expiratory muscle training.